Thermotropic behavior of lithocholic acid derivative linked hydroxyethyl cellulose - Shaikh, V. A. E.; Maldar, Noormahamad N.; Lonikar, Shrikant Vitthal; Rajan, C. R.; Ponrathnam, S. (Journal of Applied Polymer Science, 2006)
Various mesogenic lithocholic acid (LA) derivatives [3-acetyl LA (LAAC); 3-propionyl LA (LAP), 3-cinnamoyl LA (LACin); 3-benzoyl LA (LAB), 3-(4-nitrobenzoyl) LA (LANB); and methyl-3-(3-carboxypropionyl) LA, i.e., LA methyl ester monosuccinate (LAMeMS)] were reacted with hydroxyethyl cellulose (HEC) to obtain a series of LA derivatives of HEC. These polymers were characterized by the mesogen content, 1.1, differential scanning calorimetry, and hot-stage coupled polarizing optical microscopy. The degree Of Substitution (DS) ranged from 0.27 to 1.11. Polymers HEC-LAB (DS = 1.11), HEC-LANB (DS = 0.80), HEC-LACin (DS = 0.76), and HEC-LAP (DS = 0.27) exhibited a mesophase on heating whereas HEC-LAB also showed a mesophase on cooling. The other polymers HEC-LAAC (DS = 0.89) and HEC-LAMeMS (DS = 0.36) did not reveal mesophase formation with either heating or cooling. It is observed that the formation of a mesophase is affected by the type of mesogen that is used rather than the mesogen content of the polymer. (c) 2006 Wiley Periodicals, Inc.
Keywords: hydroxyethyl cellulose; lithocholic acid; thermotropic

Cholesterol-linked beta-cyclodextrin - a thermotropic liquid-crystalline derivative - Shaikh, Vasi Ahmed Ebrahim; Lonikar, Shrikant Vitthal; Dhoble, Deepa Arun; Pawar, G. M. (Bulletin of the Chemical Society of Japan, 2007)
Liquid-crystalline derivative of ss-cyclodextrin (BCD) was prepared by covalent linking of monocholesteryl succinate (ChMS) with ss-cyclodextrin. To the best of our knowledge, this was first ever attempt so far of its kind, in which BCD has been converted into its liquid-crystalline derivative through covalent linkage of a mesogen. The degree of substitution (DS) obtained was approximate to 2.00. The product was characterized by various techniques, such as FT-IR, NMR, DSC, hot-stage-coupled optical polarizing microscopy (OPM), microanalysis and chemical methods. Cholesterol-linked ss-cyclodextrin (CDCh) derivative was found to exhibit thermotropic liquid-crystalline behavior. The product exhibited birefringence during first heating above 130 degrees C, and it became isotropic at about 180 degrees C, whereas the parent compound BCD decomposed without melting above 250 degrees C. A comparison of CDCh derivative to similar liquid-crystalline polysaccharide derivatives is presented.